Timed Automation Petri Nets for Time-Delay Automation Systems - Sener, Ibrahim; Cansever, Galip (IEEE, 2016)
In this study, a new type of Petri net, which consists of a combination of Timed Petri nets (TPN) and Automation Petri Nets (APN), is introduced. This new Petri net, called timed automation Petri nets, (Timed APN), is obtained by adding time delays to automation Petri nets. Time delays, which may occur in automation systems, can be easily represented in TPN. Although APN is a powerful modeling and designing method in automation systems, it is not capable of representing time delays contrary to TPN. With the addition of time delay, a more powerful type of Petri net, which can be used for time delay automation systems, is obtained and so time-delay automation systems will be modeled in a more effective way by using this new petri net.
Keywords: Engineering